2021
DOI: 10.1101/2021.05.18.444665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Encoding of inflammatory hyperalgesia in mice spinal cord

Abstract: Inflammation modifies the input-output properties of peripheral nociceptive neurons, thus leading to hyperalgesia, i.e., changes in the perception of noxious heat stimuli such that the same stimulus produces enhanced pain. The increased nociceptive output enters the superficial dorsal spinal cord (SDH), which comprises the first CNS network integrating the noxious information. Here we used in vivo calcium imaging and a computational approach to investigate how the SDH network in mice encodes the injury-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…However, we cannot exclude peripheral sensitization, such as sensitization of tactile C-fibers in pruritic skin in BRP (Hashimoto and Yosipovitch, 2019). Since we found the most extensive branching in the two pruritic areas with alloknesis, increased excitability (Barkai et al, 2020;Wong et al, 2022) and an expanded receptive field by increased branching could enhance the spinal pruriceptive input inducing alloknesis (Finnerup et al, 2021).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, we cannot exclude peripheral sensitization, such as sensitization of tactile C-fibers in pruritic skin in BRP (Hashimoto and Yosipovitch, 2019). Since we found the most extensive branching in the two pruritic areas with alloknesis, increased excitability (Barkai et al, 2020;Wong et al, 2022) and an expanded receptive field by increased branching could enhance the spinal pruriceptive input inducing alloknesis (Finnerup et al, 2021).…”
Section: Discussionmentioning
confidence: 74%
“…This again suggests an underlying hypersensitivity in the patients, which can already be observed in the healthy-appearing skin of the patients. Importantly, sensitization to electrical stimulation by extreme branching (Barkai et al, 2020;Wong et al, 2022) might primarily increase the pain sensation and thus explain the combination of higher pain ratings and lower innervation density in BRP as compared to HCs. In line with this, in patients with type 2 diabetes, immunofluorescence staining of GAP-43, a marker of neuronal regeneration, showed that they had more pain with increased branching of GAP-positive fibers (Galosi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In pathological conditions, such as inflammation or nerve injury, primary afferents become hyperexcitable, thus modifying the rate and timing of their firing toward the nociceptive dorsal horn network 9,[16][17][18][19] . There, it produces overall increased activity of dorsal horn interneurons [20][21][22] , resulting in amplified activation of PNs [23][24][25] , thus enhancing the output of the first CNS nociceptive networks to higher centers and leading to increased nociception and pain [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%